Fleksibilitas versus Ketergantungan: Kontribusi BLU bagi Peningkatan Mutu Pendidikan di Indonesia - Rizkiyyan, Muhammad Fathan (TSAQOFAH, 2026)
This article examines the role and contribution of the Badan Layanan Umum (BLU) model in improving the quality of education in Indonesia. Employing a qualitative research method through a literature study (library research), the study analyses the implementation of Badan Layanan Umum in various educational institutions, including public universities and vocational schools. The findings indicate that Badan Layanan Umum status provides educational institutions with greater financial autonomy and managerial flexibility, thereby enabling more responsive budgeting, reinvestment of funds in facility development and research, and the application of performance-based management systems. Case studies in several institutions suggest positive impacts on service quality and financial independence. Nevertheless, challenges remain, including a high level of dependence on government funding and the need to strengthen managerial capacity. The study concludes that Badan Layanan Umum is a strategic policy instrument for enhancing educational services, but it still requires continuous evaluation and policy reinforcement to optimally support improvements in the quality and governance of education in Indonesia.